Spatial Assessment of Degraded Lands for Biofuel Production in Indonesia - Wanggi Jaung; Wiraguna, E.; Okarda, B.; Artati, Y.; Chun, S.G.; Syahru, R.; Leksono, B.; Prasetyo, L.B.; Lee, S.M.; Baral, H. (MDPI, 2018)
This study spatially estimated degraded lands in Indonesia that have limited functions for food production, carbon storage, and conservation of biodiversity and native vegetation and examined their suitability to grow biodiesel species (Calophyllum inophyllum, Pongamia pinnata, and Reutealis trisperma) and biomass species (Calliandra calothyrsus and Gliricidia sepium). Results showed ~3.5 million ha of degraded lands potentially suitable for these species in Indonesia. With the all-five-species scenario, these lands had the potential to produce 1105 PJ year−1 of biomass and 3 PJ year−1 of biodiesel. With the biodiesel-only-species scenario, these lands showed the potential to produce 10 PJ year−1 of biodiesel. Despite this energy potential, however, the land sizes were too small to support economies of scale for biofuel production. The study findings contribute to identifying lands with limited functions, modeling the growth of biofuel species on regional lands, and estimating carbon stocks of restored degraded lands in Indonesia.